Experimental and analytical analysis of a post-tensioned timber frame under horizontal loads. (15th April 2016) - Wanninger, F.; Frangi, A.
Highlights: Static pushover tests on a post-tensioned timber frame. Experimental analysis including an investigation in the connection behaviour. An analytical solution is provided by a simple spring based model. Comparison between the pushover-tests and the model prediction. Abstract: Post-tensioned timber frames are investigated at ETH Zurich in the context of the development and promotion of efficient hybrid timber structures made of hardwood. These structures can be prefabricated and are quickly assembled on site, making them suitable for multi-storey buildings. A post-tensioned timber frame with hardwood reinforcement was analysed with a series of static pushover-tests. The frame was loaded with a horizontal force while the displacement was recorded. The results of these pushover-tests are presented herein and will be compared with pushover-curves obtained from an analytical spring model. Attention will be given to the behaviour of the beam–column connections, where several LEDs were attached to analyse the connection behaviour and the influence of the tendon force on the lateral stiffness of the frame. All tests were performed with a controlled load level, which was estimated using a simple analytical spring model. The test verified the analytical spring model and showed the self-centring behaviour of such structures.